Pengaruh profitabilitas, struktur modal, ukuran perusahaan, dan kebijakan dividen terhadap nilai perusahaan - Ilham Bangkit Priambudi; Fitri Laela Wijayati (Journal of Economics and Business Research (JUEBIR), 2023)
This study aims to analyze the effect of profitability, capital structure, company size, and dividend policy on company value. This study was conducted on companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The data used is secondary data from the company's annual report. The sampling technique is purposive sampling, obtained research samples of 50 data. The research method used is a quantitative research method using technical data analysis, namely regression analysis of panel data, while for data processing using the Eviews 10 program. The results showed that profitability, capital structure, and dividend policy have a positive effect on the value of the company. While the size of the company negatively affects the value of the company